The role of the future physician: building on shifting sands - Fernandes, Linford; FitzPatrick, Michael EB; Roycroft, Matthew (Clinical medicine (London, England), 2020)
The role of the future physician in the NHS is of interest to current doctors, patients, policymakers and the wider public. Amid the COVID-19 pandemic, it has never been more clear that the healthcare needs of the population, and the technical and scientific advances with which to solve them, are rapidly evolving and the medical workforce must adapt to these changes to deliver personalised healthcare. This article considers the current challenges that need to be addressed to deliver a future physician-led healthcare service that works for its patients. Key themes are expanded upon, including the changing healthcare workforce, digital and technological innovation, service delivery, complex conditions and changing patient demographics. The impact and challenges of the ongoing COVID-19 pandemic on these factors are highlighted. Avenues for development are suggested, both in postgraduate medical training and the health service as a whole. These changes will be required to deliver the physicians of the future, imbued with the skills and attributes they will need to provide a high standard of care in the mid-21st century.